Multi-scale characterization of tight carbonate rocks based on digital cores - Wang, Changsheng; Tian, Lili; Sun, Chuanrui; Deng, Yuwei; Zhou, Ying; Nie, Xin (Frontiers in Earth Science, 2025)
The characterization of carbonate microstructure is of great significance for the evaluation of carbonate oil and gas resources. However, due to the complexity and heterogeneity of the pore structure of tight carbonate rocks, high-pressure mercury intrusion, nuclear magnetic resonance (NMR) and other methods have different limitations in the characterization. This study takes tight carbonate core samples in the fourth member of the Ordovician Majiagou Formation in the Ordos Basin as the research object, and the rock physics experiments, computed tomography (CT), high resolution large-scale backscatter scanning electron microscopy (MAPS), quantitative evaluation of minerals by scanning electron microscopy (QEMSCAN) and focused ion beam-scanning electron microscopy (FIB-SEM) was utilized to characterize the pore structure from micrometer to nanometer, revealing the main mineral composition, and systematically analyzing the relationship between different mineral and pore structures. The results show that the microscopic reservoir space in the study area is mainly composed of inter-crystalline pores, intra-crystalline pores and microfractures; there are obvious differences in the pore structure of different lithologies. The samples with more dolomite have the largest number of pores and throats, the largest coordination number, and the best connectivity; the samples with more calcite have the smallest pore radius. The presence of quartz is conducive to the preservation of pores. This multi-scale characterization method using digital core technology provides us with comprehensive pore characteristic, provides important clues for further understanding the pore structure of tight carbonate reservoirs.